Immune repertoire and evolutionary trajectory analysis in the development of diabetic nephropathy - Ye, Zheng; Zhang, Yidi; Huang, Nan; Chen, Shen; Wu, Xiaodong; Li, Ling (Frontiers in Immunology, 2022)
Diabetic nephropathy (DN) is the leading cause of death and the greatest risk to the lives of people with advanced diabetes. Yet, the molecular mechanisms underlying its development and progression remain unknown. In this research, we studied the primary pathways driving DN using transcriptome sequencing and immune repertoire analysis. Firstly, we found that the diversity and abundance of the immune repertoire in late DN were significantly increased, while there was no significant change in early DN. Furthermore, B cell-mediated antibody responses may be the leading cause of DN progression. By analyzing master regulators, we found the key DN-driving transcription factors. In the late stage of DN, immune cells, fibroblasts, and epithelial cells were abundant, but other stromal cells were few. Early DN kidneys had a higher tissue stemness score than normal and advanced DN kidneys. We showed that DN progression involves proximal tubular metabolic reprogramming and stemness restoration using Monocle3. Through WGCNA, we found that co-expression modules that regulate DN progression and immune repertoire diversity mainly regulate immune-related signaling pathways. In addition, we also found that early DN had apparent activation of immune-related signaling pathways mainly enriched in immune cells. Finally, we found that activation of fibroblasts is typical of early DN. These results provide a research basis for further exploring the molecular biology and cellular mechanisms of the occurrence and development of DN and provide a theoretical basis for the prevention and treatment of DN.